ASSESSMENT OF THE DEGREE OF INTOXICATION AND THE FORECAST LEVEL OF THE INTEGRAL INDEX OF INTOXICATION UNDER CERTAIN INFECTIOUS DISEASES - M. Y. Marzhokhova; M. M. Nagoeva; M. M. Afashagova; A. R. Marzhokhova; A. A. Shaova (Архивъ внутренней медицины)
The Purpose of this research was to study indicators syndrome of endogenous intoxication in patients with erysipelas and herpes infection that can be used to predict relapse in these diseases.Based on the goal were examined in 54 patients with primary, erythematous form of erysipelas of different localization and 42 patients with the localized form of herpes infection in the dynamics of these diseases.Determined the level of substances of low and medium molecular weight (HV and SMM), and oligopeptides, as well as the Integral index of intoxication by the method of M. I. Malakhov (1994) and Lowry (1991). To assess the value of the Integral index of intoxication in the prediction of relapses were calculated odds ratio.Revealed the dependence of studied parameters of disease and completeness of recovery.Level measurement HV and SMM and oligopeptides allows us to calculate the Integral index of intoxication, which can be used as a prognostic criterion of recurrence as erysipelas, and herpes infection.